Photocatalytic Degradation of Ethylene Bis-Dithiocarbamate Fungicide from Wastewater Using Cerium Oxide Nanoparticles under Natural Solar Irradiation - Danjuma, Mahadi; Abbaraju V.D.N. Kumar, Dr.; Nutulapati, Venugopal V.S. (Malaysian Journal of Science, 2024)
This study developed a suitable method for the degradation of ethylene bis-dithiocarbamate pesticide mancozeb in wastewater and agricultural runoff using nanoceria as photocatalysts. The nanoceria or cerium oxide nanoparticles were synthesized using a simple coprecipitation method with cerium nitrate hexahydrate (Ce (NO3)3. 6H2O) and Potassium carbonate (K2CO3) as a precursor and precipitating agent respectively. The synthesized powder particle was further ascertained through characterization using Scanning Electron Microscopy SEM for surface morphology, Fourier Transform Infrared Spectroscopy FTIR for the determination of the functional groups, Powder X-ray diffraction PXRD for crystal structure, phase and crystallite size and Energy Dispersive X-ray Spectroscopy EDAX for elemental composition of the synthesized nanoceria. It was revealed that the nanoparticle was successfully synthesized with a crystallite size of 27 nm. Photocatalytic degradation of mancozeb pesticide using the synthesized NPs was determined in batches with optimization of certain parameters including; the initial concentration of pesticide, quantity of the photocatalyst, irradiation time, calcination temperature and UV index. Nanoceria was found to degrade more than 62% of the initial concentration of mancozeb in 2 hours. Nanoceria usually acts as an active sorbent in the destruction of pesticides in wastewater and as such, its application on the degradation of mancozeb is crucial and significant. This method can be suitable for agricultural runoff and synthetic chemical pesticides effluent with proper optimisation.